E-COURT AS THE PREVENTION EFFORTS AGAINST THE INDONESIA JUDICIAL CORRUPTION - Susanto Susanto (Yustisia Jurnal Hukum, 2020)
This study aims to determine the effectiveness of the use of E-Court to eliminate judicial corruption activities. Actions or policies permitted by law and which are not permitted. Corruption in the administration sector is closely related to the relationship between justice seekers and individual administrative staff. The issues raised in this study are How is the systematic E-Court in Suppressing Judicial Corruption in Case Administration Management in Courts in JABODETABEK and How to Improve Administrative Management of Courts in the Future. This study uses an empirical method approach with descriptive analytical research specifications. This is because this study seeks to describe the facts of the E-Court System Effectiveness in the field of suppressing Corruption in the Court's administrative management sector and the factors faced so that it can finally describe the concept of implementing a clean court management system with technology and improvement efforts. The concept of public services must be well understood by the judiciary, because until now there are still many complaints about legal services originating from the justice seeker community. The functionalization of E-Court is not optimal because there are still many justice seekers who still do not know the existence and use of the system. The E-Court system is expected to support the realization of judicial principles that are fast, simple and inexpensive in managing case administration